2012
DOI: 10.1002/eji.201242627
|View full text |Cite
|
Sign up to set email alerts
|

Mature proteins derived from Epstein–Barr virus fail to feed into the MHC class I antigenic pool

Abstract: The immediate presentation of peptide epitopes on MHC class I (MHC I) after antigen expression has led to the concept that MHC I ligands are mostly derived from defective ribosomal products (DRiPs), a subset of newly synthesized proteins that are rapidly degraded by the proteasome. Whether and to what extent mature proteins contribute to the antigenic pool, however, has remained elusive. Here, we developed a conditional antigen expression system that allows studying antigen presentation from mature proteins by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
(33 reference statements)
2
14
0
Order By: Relevance
“…1E). We and others have previously observed this phenomenon, and the data suggest that some inherently destabilized form of newly synthesized SCRAP-SVG is degraded and presented, despite the presence of a saturating dose of Shield-1 (17,21,26). This meets the definition of a defective ribosomal product (DRiP) (27), which are important sources of peptides for the antigen presentation pathway (28,29).…”
Section: Resultsmentioning
confidence: 57%
“…1E). We and others have previously observed this phenomenon, and the data suggest that some inherently destabilized form of newly synthesized SCRAP-SVG is degraded and presented, despite the presence of a saturating dose of Shield-1 (17,21,26). This meets the definition of a defective ribosomal product (DRiP) (27), which are important sources of peptides for the antigen presentation pathway (28,29).…”
Section: Resultsmentioning
confidence: 57%
“…In these experiments, terminating the synthesis of several EBV antigens (including EBV nuclear antigens), and the LCMV nucleoprotein, resulted in a partial or complete loss of antigen presentation, even when the cells contained pools of mature protein [40,5557]. While these results appear consistent with a major contribution from newly synthesized proteins, there are some caveats.…”
Section: The Contribution Of Newly Synthesized Proteins To Antigen Prmentioning
confidence: 87%
“…For LCMV (nucleoprotein) and EBV (EBNA1) viral antigens it was reported that when Tet was removed and antigen synthesis was terminated, the presentation of some peptides decreased at times when there was still a substantial pool of mature protein (46, 47). Similarly, while this manuscript was in preparation, it was reported for a tet-inducible FKBP-EBV antigen system that mature antigen did not contribute to antigen presentation (25). It is possible that these antigens are ones where the contribution from DRiPs is more substantial.…”
Section: Discussionmentioning
confidence: 77%
“…In order to bind Shield these constructs must be properly folded and therefore by definition are not DRiPs (11, 19). Shield was shown to selectively stabilize FKBP fusions without affecting other cellular processes (19, 23, 24), and has been used by others to study antigen presentation (11, 12, 25). We fused FKBP to the copepod green fluorescent protein (copGFP).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation